Doubtful swelling on clinical examination reflects synovitis in rheumatoid arthritis. (June 2020) - Mandl, Peter; Studenic, Paul; Supp, Gabriela; Durechova, Martina; Haider, Stefanie; Lehner, Michaela; Stamm, Tanja; Smolen, Josef S.; Aletaha, Daniel
Aims: The aim of this study was to evaluate the implication of doubtful joint swelling on clinical examination with respect to objective markers of synovitis by ultrasound (US) in patients with rheumatoid arthritis (RA). Methods: Two independent observers performed a modified 28 swollen joint assessment (28SJC), in which joints could be graded as either definitely swollen, non-swollen, or doubtfully swollen. Two examiners blinded to clinical information performed US assessment of the hands. We performed descriptive statistics and models to analyse the links between clinical assessment and objective markers of inflammation. Results: A total of 1204 joints were evaluated in 43 RA patients; 93% (40/43) of patients had ⩾1 joint with doubtful swelling (range: 0–4/patient). Inter-reader reliability for the modified 28SJC was good (0.74). Generally, both grey scale (GS) and power Doppler (PD) discriminated across not swollen, doubtful, and swollen joints. GS signals discriminated better than PD between doubtful swelling and no swelling [odds ratio (OR) for GS: 5.2; 95% confidence interval (CI) 1.2–23.3 versus OR for PD 1.7; 95% CI 0.2–13.0], whereas PD discriminated better than GS between swelling and doubtful swelling (OR for PD: 28.7; 95% CI 3.6–228.2 versus GS: 1.7; 95% CI 0.3–8.4). Joint osteophytes did not increase the degree of doubtfulness. Conclusion: Clinical doubt in the assessment of joint swelling constitutes an intermediate state between unequivocal swelling and the lack thereof also regarding the objectively quantified level of inflammation. In order to increase sensitivity for joint inflammation, the historical clinical approach of considering doubtful swelling the absence of swelling should be revisited to interpret clinical doubtfulness as an indication of swelling.